The Influence of Sevelamer Hydrochloride and Calcium Carbonate on Markers of Inflammation and Oxidative Stress in Hemodialysis at Six Months of Follow-Up - Díaz-De la Cruz, Elodia Nataly; Cerrillos-Gutiérrez, José Ignacio; García-Sánchez, Andrés; Prado-Nevárez, Carlos Gerardo; Andrade-Sierra, Jorge; Jalomo-Martínez, Basilio; Banda-López, Adriana; Rojas-Campos, Enrique; Miranda-Díaz, Alejandra Guillermina (Frontiers in Medicine, 2021)
End-stage renal disease (ESRD) patients present alterations in mineral and bone metabolism. Hyperphosphatemia in ESRD is considered an independent risk factor for cardiovascular disease (CVD) capable of increasing morbidity and mortality. Sevelamer hydrochloride is a calcium-free, non-absorbable phosphate-chelating polymer. Calcium carbonate chelator is useful in controlling serum phosphate levels. There is insufficient information on the influence of sevelamer hydrochloride and calcium carbonate on the behavior of oxidative stress (OS) markers and inflammation in hemodialysis (HD) patients. A randomized, open clinical trial was carried out in patients to evaluate the influence of sevelamer hydrochloride and calcium carbonate at six months of study follow-up. Levels of oxidants (LPO, NO, and 8-Isoprostanes), antioxidants (SOD and TAC), oxidative DNA damage (8-OHdG and hOGG1), pro-inflammatory cytokines (IL-6 and TNF-α), and inflammation markers (ferritin and C-reactive protein) were measured with colorimetric and ELISA methods. We found a significant increase in oxidants LPO and NO, antioxidants SOD and TAC, downregulation of IL-6 and TNF-α. Ferritin decrease at sis month follow-up in the sevelamer hydrochloride group. The increase in C-reactive protein was found in the group of patients treated with calcium carbonate. In conclusion, we found an oxidative state imbalance with an increase in LPO and NO oxidants. The activity of the antioxidant enzymes (SOD and TAC) was also found to be increased, which could suggest a compensatory effect in the face of the increase in oxidants. The same phenomenon was observed with the increase in the oxidative damage marker to DNA and the increase in the DNA repair enzyme, suggesting a compensatory effect. Pro-inflammatory cytokines were predominantly down-regulated by TNF-alpha in the group that ingested sevelamer hydrochloride in the final determination at six months of follow-up. The management of hyperphosphatemia with sevelamer hydrochloride appears to have obvious anti-inflammatory and antioxidant benefits.